Eremophila maculata-isolation of a rare naturally-occurring lignan glycoside and the hepatoprotective activity of the leaf extract - Youssef, Fadia S.; Sobeh, Mansour; Wink, Michael (Phytomedicine, 2016)
BACKGROUND: The Australian plant Eremophila maculata F. Muell (Scrophulariaceae) is cultivated worldwide as an ornamental plant. PURPOSE: This study was designed to assess the antioxidant and hepatoprotective activities of a methanol extract from E. maculata leaves (EMM) both in vitro and in vivo (rats) experiments. Detailed phytochemical study was done on the extract followed by molecular docking experiments on TNF-α ascertain the efficacy of the isolated compounds. METHODS: The antiproliferative activity was evaluated in the human cancer cell lines A-495, PC3 and HepG2 cells using the SRB method. The antioxidant activitywas evaluated in vitro using the DPPH• assay while the hepatoprotective properties were investigated by determining the amelioration of CCl4-induced cytotoxicity and oxidative stress in HepG2 cells. The activity was confirmed in vivo by studying tamoxifen-induced hepatotoxicity in rats. An in-depth phytochemical investigation of a methanol extract was performed using 1D and 2D NMR experiments. In silico molecular modeling studies of the isolated compounds on TNF-α (PDB ID 2AZ5) were carried out using Discovery Studio 2.5 software applying C-Docker protocol. RESULTS: The IC50 values of EMM were >500µg/ml for both PC3 and HepG2 cells indicating its safety. Similar to the standard drug silymarin, EMM could restore AST, ALT values; replenish GSH level, SOD activity and TAC in vitro. The hepatoprotective activity was confirmed in vivo in which the extract (20mg/kg body weight) decreased ALT and AST levels by 45.23 and 45.79%, respectively as compared to the tamoxifen treated groups. Oxidative stress was reduced by lowering of thiobarbituric acid reactive substances by 28.57%. Additionally, hepatocyte inflammation was improved by reducing the pro-inflammatory mediator TNF-α by 54.29%. Phytochemical investigation resulted in the isolation of a rare naturally-occurring lignan glycoside, namely pinoresinol-4-O-[6″-O-(E)-feruloyl]-β-D-glucopyranoside for the first time from the Scrophulariaceae in addition to 12 known compounds.Pinoresinol-4-O-[6''-O-(E)-feruloyl]-β-D-glucopyranoside was the strongest inhibitor of TNF-α as evidenced from its higher fitting scores comparable to lead compound. CONCLUSIONS: These findings highlighted for the first time that EMM could be an interesting candidate as a safe, natural liver supplement for relieving of various hepatic disorders and counteracting the effect of many xenobiotics.